The Party Is Over: Policy Switch and Party Dismantling in Moreno’s Ecuador - Resmini, Fabio (Springer, 2025)
Why do parties break down? The literature on party development generally assumes that parties collapse as an unintended consequence of strategic mistakes on the part of their leadership. This article shows that the demise of a party can in fact be a direct consequence of the leader’s deliberate actions to undermine it. Through an investigation of the dramatic downfall of Alianza PAIS, the most electorally successful party in Ecuador’s history, the article puts forward a theory of party dismantling—i.e., the process through which a leader intentionally deprives their party of the resources necessary for it to thrive with the purpose of undermining it. The article marshals evidence from 46 interviews, newspaper articles, documents, and roll call votes to accomplish two goals: first, to demonstrate how, after his bait-and-switch to a neoliberal policy agenda, President Moreno (2017–2021) effectively dismantled Alianza PAIS to pursue his policy goals; and second, to show that three conditions are causally important for party dismantling to happen: a top-down party structure, support from actors outside the party, and opposition from within the party to the leader’s policy agenda, contributing to the literature on party development by shedding light on an understudied path towards party breakdown.
Keywords: Political parties; Party breakdown; Policy switch; Latin America; https://purl.org/pe-repo/ocde/ford#5.06.01